1976
DOI: 10.1159/000458856
|View full text |Cite
|
Sign up to set email alerts
|

A Reassessment of the Phospholipid Dependence of Membrane-Bound Enzymes, with Special Reference to GIucose-6-Phosphatase and Na+, K+-Dependent Adenosine Triphosphatase

Abstract: It is suggested that the specific involvement of phospholipid in either the expression or constraint of glucose-6-phosphatase activity is not conclusively established by the existing experimental evidence. The physiological significance of an apparent requirement for phosphatidylserine for Na+, K+-dependent adenosine triphosphatase activity is also questioned. The need for a critical reassessment of past conclusions in the light of present knowledge is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…This increase was not apparent when the enzyme was assayed in the absence of detergent. Our finding supports the concept that deoxycholate potentiates the fasting response (3,7). This is more evident after 48 h fasting, where the liver enzyme levels are approximately 1.5-fold of control values when assayed in the absence of deoxycholate but increases up to 1.8-fold when assayed in its presence.…”
Section: Methodssupporting
confidence: 89%
“…This increase was not apparent when the enzyme was assayed in the absence of detergent. Our finding supports the concept that deoxycholate potentiates the fasting response (3,7). This is more evident after 48 h fasting, where the liver enzyme levels are approximately 1.5-fold of control values when assayed in the absence of deoxycholate but increases up to 1.8-fold when assayed in its presence.…”
Section: Methodssupporting
confidence: 89%
“…Exposure of pure UDP-glucuronyltransferase to similar treatment with phospholipase C did not cause any measurable enzyme inhibition, presumably because of the virtual absence of phospholipid bound to the pure transferase. Duck-Chong (1976) suggested that membrane-bound enzyme activities may be supported by the presence of detergents acting as lipid substitutes. Furthermore, Lu et al (1974) showed that the benzphetamine (N-benzyl-N'dimethylphenethylamine) N-demethylase activity of a reconstituted microsomal enzyme system was stimulated when a number of detergents were substituted for a crude liver lipid fraction in the reconstituted system: some detergents were as effective as lipid in eliciting enzyme activity.…”
Section: Resultsmentioning
confidence: 99%